Restriction of human immunodeficiency virus type 1 by TRIM-CypA occurs with rapid kinetics and independently of cytoplasmic bodies, ubiquitin, and proteasome activity - Perez-Caballero, David; Hatziioannou, Theodora; Zhang, Fengwen; Cowan, Simone; Bieniasz, Paul D (Journal of virology, 2005)
TRIM-CypA is an owl monkey-specific variant of the retrovirus restriction factor TRIM5alpha. Here, we exploit its modular domain organization and cyclosporine sensitivity to probe the kinetics and mechanism of TRIM5-mediated restriction. Time of addition/withdrawal experiments reveal that inhibition of incoming human immunodeficiency virus type 1 capsids by TRIM-CypA occurs within minutes of their delivery to the target cell cytoplasm. However, while TRIM-CypA restriction is partly dependent on a RING domain, restriction occurs independently of the ubiquitin/proteasome system. Moreover, tagged TRIM-CypA proteins can be fully active as restriction factors without forming cytoplasmic bodies.